Pancreatitis: common but forgotten causes - E. R. Donсova; O. V. Remizov; N. V. Novoselya (Медицинский вестник Юга России, 2021)
Objective: to study the causes of pancreatitis. Materials and methods: a clinical case of acute pancreatitis during the treatment of ulcerative colitis with 5-aminosalicylic acid-containing drugs. Methods: clinical, laboratory and instrumental (biochemical blood analysis, standard coprological examination, Ultrasound examination of the abdominal cavity, Esophagogastroduodenoscopy). Results: based on the data of the clinic, laboratory and instrumental studies, a diagnosis was made: drug-induced pancreatitis associated with mesalazine intake. Ulcerative colitis, total form, high degree of activity. Duodenal ulcer disease associated with Helicobacter pylori, unstable remission. Erosive bulbitis. The indicated therapy with polyenzyme drugs, proton pump inhibitors, antispasmodics, and glucocorticosteroids resulted in the resolution of clinical manifestations and the normalization of altered laboratory parameters. Conclusions: the use of 5-aminosalicylic acid preparations for the treatment of ulcerative colitis may be associated with the development of pancreatitis, which must be taken into account in clinical practice.